Reasons for cannabidiol use: a cross-sectional study of CBD users, focusing on self-perceived stress, anxiety, and sleep problems - Julie Moltke; Chandni Hindocha (BMC, 2021)
Abstract Background Public and medical interest in cannabidiol (CBD) has been rising, and CBD is now available from various sources. Research into the effects of low-dose CBD on outcomes like stress, anxiety, and sleep problems have been scarce, so we conducted an online survey of CBD users to better understand patterns of use, dose, and self-perceived effects of CBD. Methods The sample consisted of 387 current or past-CBD users who answered a 20-question online survey. The survey was sent out to CBD users through email databases and social media. Participants reported basic demographics, CBD use patterns, reasons for use, and effects on anxiety, sleep, and stress. Results The sample (N = 387) consisted of 61.2% females, mostly between 25 and 54 years old (72.2%) and primarily based in the UK (77.4%). The top 4 reasons for using CBD were self-perceived anxiety (42.6%), sleep problems (42.5%), stress (37%), and general health and wellbeing (37%). Fifty-four per cent reported using less than 50 mg CBD daily, and 72.6% used CBD sublingually. Adjusted logistic models show females had lower odds than males of using CBD for general health and wellbeing [OR 0.45, 95% CI 0.30-0.72] and post-workout muscle-soreness [OR 0.46, 95%CI 0.24-0.91] but had higher odds of using CBD for self-perceived anxiety [OR 1.60, 95% CI 0.02-2.49] and insomnia [OR 1.87, 95% CI 1.13-3.11]. Older individuals had lower odds of using CBD for general health and wellbeing, stress, post-workout sore muscles, anxiety, skin conditions, focusing, and sleep but had higher odds of using CBD for pain. Respondents reported that CBD use was effective for stress, sleep problems, and anxiety in those who used the drug for those conditions. Conclusion This survey indicated that CBD users take the drug to manage self-perceived anxiety, stress, sleep, and other symptoms, often in low doses, and these patterns vary by demographic characteristics. Further research is required to understand how low doses, representative of the general user, might impact mental health symptoms like stress, anxiety, and sleep problems.